Dielectric, electrical conductivity, and thermal stability studies of cellulosic fibers reinforced polylactic acid composites - A., N. Azaharia; M. J., M. Ridzuan; M. S., Abdul Majid; A. B., Maslinda; Cheng, E. M.; Khor, S. F.; M. T., A. Rahman; M. H., Sulaiman (Taylor and Francis, 2022)
In this study, biodegradable polylactic acid (PLA) composites were reinforced with three different natural fibers, were bamboo (BF), sugarcane (SF), and banana pseudostem (BPF) fibers, and prepared at different loadings (10, 20, and 30 wt.%). The solvent casting particulate leaching method was implemented to produce porous composites, and salt was used as the particulate material. The dielectric properties of the PLA/BF, PLA/SF, and PLA/BF composites were studied for different loadings of cellulosic fibers. The composites were observed using scanning electron microscopy (SEM), and the PLA composites with 30 wt.% filler content were analyzed using Fourier transform infrared (FTIR) and thermogravimetric analysis (TGA). According to the dielectric tests, all PLA/BF, PLA/SF, and PLA/BPF composites have low dielectric constants and dielectric loss. The PLA/BF composites exhibited the highest dielectric constant, dielectric loss, and electrical conductivity, followed by the PLA/BF and PLA/SF composites. The morphology of the composites showed their porous structure. The FTIR spectra showed the main constituents presented in the composites, and the PLA/BF showed higher thermal stability than the other composites.